TAVERNS IN INDRA IN THE 1930s FROM A HISTORICAL POINT OF VIEW - Krēgere, Olga (Via Latgalica, 2008)
Based on the sources and literature available to the author, as well as on data obtained during field study, the paper describes the origins and functions of a tavern in Daugavpils region (now Kraslava region) in the rural Indra municipality in the 1930s. The chronology of the paper is determined by the founding of the establishment in 1929 and its operation until 1940 when Latvia was occupied by the USSR army. The paper is organized into three topical parts: first, the origins of the tavern are described, then the environment and its development over time, and finally the fulfillment of the tavern’s objectives in the economic and cultural life. The paper is based on the following: 1) documents of the Latvian State Historical Archives (hereinafter LSHA): The 1935 census materials of the State Statistics committee; Orders to the authorities issued by the head of the administration of Daugavpils County; Notices of the Indra rural municipality (until 1937 Piedruja rural municipality) to the head of the administration of Daugavpils Region; Lists of taxpayers (1929–1940); Population statistics (1941– 1943), 2) Audiotape-recorded narrations of the tavern building heir Anna Šiško obtained during Rezekne University College’s (2007), as well as factual material obtained during the interview (2008). Judging by Jānis Šiško’s family’s purposeful construction of the tavern and its role in Indra’s economic and social culture in the 30’s of the 20th century, it can be considered that its main function was customer service. The operation and the use of the tavern was adjusted to the particular needs of the social life according to the conditions during that period. The location of the tavern within reach of the railway station and the market square provided advantageous lodging and recreation facilities. These were used by the buyers of agricultural goods and corners, called „uzkupči”, arriving on a regular weekly basis from far away, mainly from Riga, by the producers of these goods from the wide neighbourhood, as well as by local farmers in the periods of supply and sale of sugar-beet, flax, and live stock. Therefore, the operation of the tavern contributed greatly to the economic activity of the municipality. Organized recreation – dances and open-air parties in the tavern yard on the playground and in the specially arranged spacious premises of a shed with the border guards brass band, and regular theatre performances and celebrations at the occasion of public holidays – introduced the tavern to the social life of Indra and made it a popular entertainment place in the finest sense of the word and thereby contributed to the enrichment of the county’s cultural life.